Anaesthetic efficacy of 2% lidocaine with different concentrations of epinephrine (1:80, 000 and 1:200, 000) in intraligamentary injection after a failed primary inferior alveolar nerve block: a randomized double-blind study. (18th May 2020) - Aggarwal, Vivek; Singla, Mamta; Saatchi, Masoud; Hasija, Mukesh
Abstract: Introduction: The present study evaluated the anaesthetic efficacy of 2% lidocaine with 1:80, 000 epinephrine vs. 2% lidocaine with 1:200, 000 given as supplemental intraligamentary injections after a failed inferior alveolar nerve block (IANB) in patients with symptomatic irreversible pulpitis. The effect of these solutions on the heart rate was also evaluated. Methods: One-hundred-eighteen adult patients with symptomatic irreversible pulpits in a mandibular first or second molar, received an initial IANB with 2% lidocaine with 1:80, 000 epinephrine. Pain during the endodontic treatment was assessed using a visual analogue scale (Heft-Parker VAS). Eighty-eight patients with unsuccessful anaesthesia were randomly allocated to one of the two treatment groups: one group received 0.6 mL/root of supplementary intraligamentary injection of 2% lidocaine with 1:80, 000 epinephrine; while the second group received 2% lidocaine with 1:200, 000 epinephrine. Endodontic treatment was re-initiated. Success after primary injection or supplementary injection was defined as no or mild pain (pain score ≤54 mm on HP VAS) during access preparation and root canal instrumentation. Heart rate was monitored using a finger pulse oximeter. The anaesthetic success rates were analyzed with the Pearson chi-square test at 5% significance levels. The heart rate changes were analyzed using the t-test. Results: The anaesthetic success rate in patients receiving supplementary intraligamentary injections in 1:80, 000 epinephrine group was 82%, while the intraligamentary injections with 2% lidocaine with 1:200, 000 epinephrine were successful in 57% of cases. The difference was statistically significant (χ 2 =6.4, p  = .011). There was no significant effect of both the anaesthetic agents on the mean heart rate. Conclusions: Both 2% lidocaine with 1:80, 000 epinephrine and 2% lidocaine with 1:200, 000 epinephrine improved the success rates after a failed primary anaesthetic injection. The 1:80, 000 epinephrine group was significantly more successful.